Analysis of false‐positive results of fetal RHD typing in a national screening program reveals vanishing twins as potential cause for discrepancy. (19th May 2015) - Thurik, F. F.; Ait Soussan, A.; Bossers, B.; Woortmeijer, H.; Veldhuisen, B.; Page‐Christiaens, G. C. M. L.; de Haas, M.; van der Schoot, C. E.
Abstract Objectives We aim to elucidate causes of false‐positive fetal RHD screening results obtained with cell‐free DNA. Methods Fetal RHD screening was performed in 32 222 samples from RhD‐negative women by multiplex real‐time PCR in triplicate for RHD exons 5 and 7 using cell‐free DNA isolated from maternal plasma obtained in the 27th gestational week. PCR results were compared with cord blood serology in 25 789 pregnancies (80.04%). False‐positive cases were analyzed. Known biological causes (RHD variant genes), technical causes of discordance, and errors around blood sampling were investigated with leukocyte DNA from maternal and cord blood, and cell‐free DNA from stored maternal plasma. Results Not only RHD but also Y‐chromosome (DYS14) sequences were present in four plasma samples from RHD‐negative women bearing an RHD‐negative girl. Sample mix‐up and other sampling errors could be excluded in three samples. Conclusions These results indicate that false‐positive fetal RHD screening results can be caused by cell‐free DNA fragments in maternal plasma derived from a third cell line that is not representative for either the maternal genome or the genome of the vital fetus. We propose that remaining (cyto)trophoblasts of a vanishing twin are the underlying mechanism, and we estimate a frequency of this phenomenon of 0.6%. © 2015 John Wiley & Sons, Ltd.